2008
DOI: 10.1111/j.1365-2109.2008.01969.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an alcohol extract from a defatted soybean meal supplemented with a casein-based semi-purified diet on the biliary bile status and intestinal conditions in rainbow trout Oncorhynchus mykiss (Walbaum)

Abstract: A feeding experiment was conducted to examine the e¡ect of a supplemental ethanol extract from a defatted soybean meal on the biliary bile status and intestinal conditions of rainbow trout Oncorhynchus mykiss. A semi-puri¢ed control diet based on casein (Cont) and three diets supplemented with the extract (ES), bovine bile salts (BS) and their combination (ESBS) were fed to trout (10 g) for 6 weeks. The growth, feed e⁄ciency ratio, fat digestibility and gallbladderand hepato-somatic indices of ¢sh fed diet ES … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 28 publications
1
30
0
1
Order By: Relevance
“…In rainbow trout fed a SBM-based diet [4] or a casein-based diet supplemented with an alcohol extract from SBM [19], supplementation of C-tau [4] and bovine gall powder [19] increased the total biliary bile acid contents to much higher levels than in fish fed fish-meal-based and casein-based control diets. However, the bile acid concentrations in the intestinal digesta of fish fed the diets supplemented with C-tau [4] and bovine gall powder [19] were lower than in the control diet groups in the above experiments [4,19]. A precise investigation of the relationship between tissue morphology and biliary and intestinal bile status of rainbow trout fed SBM and soybean ANFs is necessary.…”
Section: Discussionmentioning
confidence: 92%
“…In rainbow trout fed a SBM-based diet [4] or a casein-based diet supplemented with an alcohol extract from SBM [19], supplementation of C-tau [4] and bovine gall powder [19] increased the total biliary bile acid contents to much higher levels than in fish fed fish-meal-based and casein-based control diets. However, the bile acid concentrations in the intestinal digesta of fish fed the diets supplemented with C-tau [4] and bovine gall powder [19] were lower than in the control diet groups in the above experiments [4,19]. A precise investigation of the relationship between tissue morphology and biliary and intestinal bile status of rainbow trout fed SBM and soybean ANFs is necessary.…”
Section: Discussionmentioning
confidence: 92%
“…Low‐lipid digestibility has been previously reported when SBM was included in the diets of rainbow trout (Watanabe, Pongmaneerat, Sato, & Takeuchi, ) and yellowtail (Nguyen et al, ). Alcohol‐soluble components in soy products affect lipid digestibility (Olli, Hjelmeland, & Krogdahl, ), and the removal of these components increases their digestibility in rainbow trout (Yamamoto et al, ) and yellowtail (Nguyen et al, ). Despite the fact that SPC is generally manufactured using aqueous alcohol extraction (Peisker, ), reduced lipid digestibility has still been reported when the level of SPC in feeds is increased (Mambrini, Roem, Carvedi, Lalles, & Kaushik, ; Ustaoglu & Rennert, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, plant products often include indigestive substances called anti-nutritional factors (ANF) that exert adverse effects on fish and may even cause severe nutritional disorders in livestock (Francis, Makkar, & Becker, 2001;Gatlin et al, 2007;Zhou et al, 2018). Several studies have reported on the adverse effect of high dietary levels of soybean products in various fish species including salmonids (Baeverfjord & Krogdahl, 1996;Rumsey, Siwicki, Anderson, & Bowser, 1994;Yamamoto et al, 2008), common carp (Urán et al, 2008), zebrafish (Hedrera et al, 2013) and turbot (Bai, Gu, Xu, Xu, & Krogdahl, 2017;Bonaldo et al, 2015;Gu, Bai, Zhang, & Krogdahl, 2016). Here, specifically SBM has been proven to induce proliferative or inflammatory conditions in the distal intestinal mucosa of farmed finfish (Gu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%